PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI SIMPANAN DAN PEMBIAYAAN BERBASIS SYARIAH PADA KOPERASI DESA TANIMULYA (MENGGUNAKAN VISUAL BASIC 2013 DAN MYSQL) - Putri, Sukma Fitria; Agustina, Riska (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
The design of this sharia-based Savings and Financing Information System uses Visual Basic programming language and MySQL database. The system development method used is using the SDLC (System Development Life Cycle) approach, while for system testing using black box testing. The information system that has been implemented in the RT 03 RW 14 Cooperative of Tanimulya Village is a solution to the problems found in the system used previously... because this information system is a development of the system used in the previous system. Because this information system is a development of a system that has not been computerized to be computerized. This system has access rights that can be controlled by a login menu that functions to protect data security and can display the main menu according to the authority of the position owned by the user. In data processing, this information system functions for data entry related to principal savings, mandatory savings, wadi'ah (voluntary) savings and financing activities, so that the reports needed by the RT 03 RW 14 Cooperative of Tanimulya Village can be presented.